Reactivity studies of pincer metal complexes stabilized by a bis(1,2,3-triazol-5-ylidene)carbazolide ligand scaffold - Bezuidenhout, Daniela I. (University of Pretoria, 2018)
Thesis (PhD (Chemistry))--University of Pretoria, 2018.